2003
DOI: 10.1303/aez.2003.187
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and annual variation of summer-diapause expression in the ladybird beetle, Coccinella septempunctata (Coleoptera: Coccinellidae), in Japan

Abstract: Variation in the summer-diapause expression of the ladybird beetle, Coccinella septempunctata, among local populations and years was investigated by field observation and dissection of sampled specimens, in Japan. Only non-diapausing adults were found in Hokkaido, northern Japan, whereas diapausing adults were observed at most sites in Honshu and southward in summer. However, the non-diapausing adults were also observed in northern Honshu and at high-altitudinal sites of central Honshu. The frequency of diapau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In addition, the wide range of food habit of the E. balteatus is also considered a suitable character as an aphid predator (Mizuno et al, 1997). Large-sized ladybirds like Harmonia axyridis and Coccinella septempunctata are voracious but they tend to have summer diapause due to high temperature (Katsoyannos et al, 1997;Ohashi et al, 2003). Because these hoverfly species do not have summer diapause, it seems that they are a suitable aphid predator during the summer in particular, when the large ladybirds are less active.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the wide range of food habit of the E. balteatus is also considered a suitable character as an aphid predator (Mizuno et al, 1997). Large-sized ladybirds like Harmonia axyridis and Coccinella septempunctata are voracious but they tend to have summer diapause due to high temperature (Katsoyannos et al, 1997;Ohashi et al, 2003). Because these hoverfly species do not have summer diapause, it seems that they are a suitable aphid predator during the summer in particular, when the large ladybirds are less active.…”
Section: Discussionmentioning
confidence: 99%
“…A group of Japanese researchers has recently tackled this problem by sampling and dissecting C. s. brucki samples in Hokkaido and several regions of Honshu (Ohashi et al 2003 ). The absence of summer diapause in Hokkaido and its presence in the plains of central Honshu was corroborated.…”
Section: Northern H Onshu ( J Apan)mentioning
confidence: 99%
“…The authors rightly concluded that there is genetic variation in diapause tendency within the local populations. They suggest that diapause is prevented there if the average daily mean air temperature in July is lower than 21.5 ° C (Ohashi et al 2003 ).…”
Section: Northern H Onshu ( J Apan)mentioning
confidence: 99%
“…The great plasticity of C7 is evident also in two geographical populations of the subspecies C. septempunctata brucki in Japan. In Hokkaido in the north, hibernal diapause is induced by short days, whereas the population in central Honshu enters estivation diapause under long days and hibernates in quiescence (Sakurai et al, 1981;Okuda & Hodek, 1983;Hodek et al, 1984;Ohashi et al, 2003). Another case of plasticity in C. s. brucki has been reported recently: some adults may produce an additional generation by taking advantage of artificial substrates warmed by direct exposure to sunlight (metal cans, paper, pieces of wood) at ambient temperatures otherwise too low to permit the development of eggs and pupae (Ohashi et al, 2005).…”
Section: Voltinismmentioning
confidence: 99%